STUDENTS’ PERCEPTION OF LEARNING MANAGEMENT SYSTEM (LMS) UTILIZED IN ONLINE ENGLISH LEARNING SITUATION DURING COVID-19 PANDEMIC - Denita Azzahra Ramadania (ELLTER Journal, 2021)
This research is aimed to figure out the students’ perceptions of Learning Management Systems (LMS) that they utilized in Online English Learning Situation During Covid-19 Pandemic. Nowadays, many teachers have changed their face-to-face learning to full online learning as the impact of coronavirus outbreak. This situation creates new model of learning in which Learning Managements System or LMS becomes one of platform that are used by both teachers and students to support learning. The various LMS such as Google Classroom, Edmodo, Schoology, Moodle, and etc. are gained interest and popular in education context including English Language Learning (ELL) and Teaching (ELT). Hence, the writer tries to expose the valuable insight from the students’ perception towards those LMS by conducting a quantitative study within survey design and instruments. This research involved 125 respondents mainly from Jabodetabek area. After the data has been collected, the writer analyzed it by using Ms. Excel 2010. The result showed a positive sight from the students. They seemed enjoy using LMS, since it facilitates students in learning English with easy features to submit assignment, quiz, feedback, and communication forum.